Fatal accidents : how prosperity and safety are linked - Lancaster, J. F. (John Frederick) (Woodhead Pub. ; CRC Press, 2009)
"In Fatal Accidents, the author contends that accidents in industry and transport diminish with the passage of time in an ordered fashion, although we are not consciously aware of this fact. Analysis of historical records of accident mortality rates, specifically in industry and transport, points toward the development of skill in avoiding mishaps. Such changes are subconsciously and collectively regulated by the population concerned - for example, by drivers in the case of road transport - and are made possible by advances in science and technology. Also included are observations of the correlation between accidents and specific measures of human activity, such as national productivity. A similar model is applicable to the reduction of general mortality rates, to economic growth and to population growth. The future cannot be predicted, but at present safety is improving at a satisfactory rate."--Publisher Web site